2020
DOI: 10.1177/2050640620924210
|View full text |Cite
|
Sign up to set email alerts
|

Proximal retroflexion versus second forward view of the right colon during screening colonoscopy: A multicentre randomized controlled trial

Abstract: Background Colonoscopy is the gold standard investigation for the detection of colorectal cancer, but the right colon is more difficult to examine than the left colon. A second examination of the proximal colon has the potential to reduce rates of missed pathology. Objective To determine whether proximal retroflexion improves the adenoma detection rate or other outcomes in the right colon compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
9
0
3
Order By: Relevance
“…Among the included studies, four studies were RCTs, [13][14][15][16] and six studies were PCSs. [17][18][19][20][21][22] All RCTs compared the impact of the second withdrawal from the right colon in RV vs. FV after a standard withdrawal during colonoscopy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the included studies, four studies were RCTs, [13][14][15][16] and six studies were PCSs. [17][18][19][20][21][22] All RCTs compared the impact of the second withdrawal from the right colon in RV vs. FV after a standard withdrawal during colonoscopy.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A previous meta-analysis 15 that included both observational studies and randomized controlled trials (RCTs) found that SFV and RF of the right colon independently increased ADR. Since then, additional RCTs have compared SFV with no SFV, and SFV with RF, in the right colon and have reported data on right colon ADR 16 17 18 19 . In order to examine this further, we have conducted an updated systematic review and meta-analysis confined only to RCTs to evaluate the role of a second examination of the right colon in improving ADR.…”
Section: Introductionmentioning
confidence: 99%
“…46 Similarly, in a recent multicenter randomized controlled trial, although a second look in the right-sided colon increased the ADR by 11% compared with standard colonoscopy in fecal immunochemical test-positive patients, a significant difference was not found between the second forward view and retroflexion groups (12% vs 9%, P Z .28). 53 Both techniques resulted in an average additional procedure time of 1.6 minutes for second visualization.…”
Section: Techniquesmentioning
confidence: 99%
“…Likewise, a right-sided sessile serrated lesion rate of 11.1% at the second examination has been demonstrated. 53 Summary: Second look, either retroflexion in the cecum or a second forward look in the proximal colon, increases ADR by up to 10 percentage points and rightsided adenoma detection by 5 percentage points.…”
Section: Techniquesmentioning
confidence: 99%